2022
DOI: 10.1177/10731911221116564
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination and Calibration Properties of the Violence Risk Appraisal Guide–Revised in a Not Criminally Responsible Provincial Population

Abstract: This study examined the discrimination and calibration properties of the Violence Risk Appraisal Guide–Revised (VRAG-R) within a large subset of the population of 574 individuals who had been found Not Criminally Responsible on Account of Mental Disorder (NCRMD) in Alberta. The VRAG-R was scored on all individuals identified via The Alberta NCR Project database from every file that contained sufficient relevant information and recidivism data were obtained via official criminal records. The VRAG-R demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The total score is used to assign a case into one of nine bins, from lowest to highest risk, each with a corresponding probability of recidivism across different follow-up periods. Based on 30 randomly selected double cases from a parallel investigation employing this sample, interrater reliability of VRAG-R scores was strong (one-way random effects model, single measure, absolute agreement): ICC A,1 = .98 (Wirove et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…The total score is used to assign a case into one of nine bins, from lowest to highest risk, each with a corresponding probability of recidivism across different follow-up periods. Based on 30 randomly selected double cases from a parallel investigation employing this sample, interrater reliability of VRAG-R scores was strong (one-way random effects model, single measure, absolute agreement): ICC A,1 = .98 (Wirove et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Violence risk appraisal guide (VRAG): 12-item actuarial risk assessment instrument for the prediction of violent recidivism. Metanalysis review of 60 studies looking at the VRAG found an AUC of 0.66-0.73 (Wirove et al, 2022).…”
Section: Why Violence Is More Than Just Mental Healthmentioning
confidence: 99%